PERAN PEMODERASI TRANSPARANSI INFORMASI : PENGHINDARAN PAJAK DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur di Indonesia) - andi Kartika; Sri Sudarsi; Moch Irsad (STIE Pelita Nusantara Semarang, 2019)
This study aims to examine and obtain empirical evidence about the effect of tax avoidance on firm value with transparency as a moderating variable in manufacturing companies listed on the Stock Exchange in 2013-2017. The data used is archived data in the form of annual reports and financial statements of manufacturing companies listed on the IDX. The results of this study indicate that tax avoidance as measured by the Effective Tax Rate (ETR) proxy which has a significant positive influence on firm value measured using Tobins' Q ratio and transparency can weaken the moderation between the effect of tax avoidance on firm value